Indoor positioning algorithm based on effective AP selection and multi-class LDA - Guiqi LIU; Zhihong QIAN; Hualiang LI; Jiani SUN; Yinuo FENG; Xue WANG (Tongxin xuebao)
To solve the problems of the lack of longitudinal position information in indoor positioning, an indoor positioning algorithm based on effective AP selection and multi-class LDA was proposed.In the offline stage, the AP selection algorithm based on stability and difference was used to extract effective AP set in the fingerprint area, and the multi-class LDA algorithm was adopted to train the fingerprint data of effective AP set at different heights to obtain longitudinal position information recognition model.In the online stage, the AP information alike the offline effective AP subset was input into longitudinal position information recognition model to obtain recognition result, and then the online fingerprint plane positioning was completed by the positioning algorithm based on the fingerprint database partition.Simulation results demonstrate that the accuracy of the proposed algorithm for determining longitudinal floors can reach 98%.